References in the correspondence of Augustine: chances and boundaries of digital “Distant reading” processes - Nunn, Christopher Alexander (Revue d'études augustiniennes et patristiques, 2016)
Analyzing Augustine’s usage of intertextual references can provide information about the kinds of texts used and modes of argumentation or about the social background of his audience. But is it also possible to make a conclusion of Augustine’s attitude towards the intellectual abilities of his correspondents? Is there a difference between his letters to women and those written to men? With the help of “Distant Reading”, it becomes evident that Augustine uses more textual references when writing to women than to men. Although only 17 letters to solely female correspondents have survived alongside 227 letters to men, letters to women are among the top five with respect to the frequency of words, total references used, or the percent of references included. Even if the marking degree of the references is considered, that is, if we focus only on explicit quotations or implicit allusions, references in letters written to women are more frequent in every case. A closer look reveals, however, that this result does not depend on Augustine’s estimation of the intellectual ability of his correspondent, but on the kind of text he is writing or Augustine’s ability to mirror the writing style of his correspondents.